I’JAZ AL-IQTISADI “ILMU AKUNTANSI DALAM AL-QUR’AN AL-KARIM” (Studi I’jaz Al-Qur’an) - Dini Nisa Usufiyah (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
Economics Miracle is a form of uniqueness and exceptionalism of the economic teachings found in the Qur’an, both implicit and explicit, which can address the challenges of the times and provide solutions to the economic problems of humanity. Accounting, based on sources from Islamic law, functions to provide important information for decision-makers. However, the misuse of accounting that does not align with the teachings of Sharia can result in the invalidity of transaction records. Therefore, the explanation of Qur’anic principles in accounting is crucial as a guide for society. Accounting activities, both textual and contextual, are outlined in the Qur’an, where the author specifically discusses the science of accounting as stated in Surah Al-Baqarah, verse 282, which clearly and thoroughly provides guidelines for accountants to produce accurate and accountable records. Using the approach of i’jāz al-iqtiṣādi, the author analyzes with the aim of contributing to accounting practices that are more in line with the teachings of the Qur’an.